2010
DOI: 10.3349/ymj.2010.51.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Estimation of Systolic Blood Pressure and Diastolic Blood Pressure Using Photoplethysmograph Components

Abstract: PurposePhotoplethysmography (PPG) is a noninvasive optical technology that detects changes in blood volume in the vascular system. This study aimed to investigate the possibilities of monitoring the cardiovascular system status by using PPG.Materials and MethodsForced hemodynamic changes were induced using cardiac stimulants; dopamine and epinephrine, and PPG components were recorded by a noninvasive method at the peripheral blood vessels. The results were compared among 6 dogs. Endotracheal intubation was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Previous studies have demonstrated that the sensitivity of BRS assessment by noninvasive means is comparable to that acquired through invasive measurement [14,25]. Digital volume pulse (DVP) signals acquired noninvasively through photoplethysmography (PPG) have been found to correlate well with changes in blood pressure [26][27][28]. Besides, the current study was designed based on the finding that baroreceptor sensitivity was impaired in subjects with chronic systemic diseases, particularly those that affect the cardiovascular system (e.g., diabetes) [2,11,17].…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the sensitivity of BRS assessment by noninvasive means is comparable to that acquired through invasive measurement [14,25]. Digital volume pulse (DVP) signals acquired noninvasively through photoplethysmography (PPG) have been found to correlate well with changes in blood pressure [26][27][28]. Besides, the current study was designed based on the finding that baroreceptor sensitivity was impaired in subjects with chronic systemic diseases, particularly those that affect the cardiovascular system (e.g., diabetes) [2,11,17].…”
Section: Complexitymentioning
confidence: 99%
“…Based on the previous finding that the change in amplitudes of DVP waveforms reflects the fluctuation in blood pressure [26][27][28] that gives rise to a corresponding compensatory change in RRI because of baroreflex, the fluctuations among successive DVP waveform amplitudes and RRIs undergo binary transformation to give two binary sequences (i.e., B Amp and B RRI , respectively).…”
Section: Computation Of Percussion Entropy Index (Pei)mentioning
confidence: 99%
“…The application of PPG has been expanding in many other researches to measure blood pressure [2], cardiac output and atherosclerosis [3,4], respiration rate [5,6] and other cardiovascular markers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, photoplethysmography (PPG) is another noninvasively optical technique that is simple, small, compact, and reasonable. PPG is broadly used in clinical monitoring, such as for cutaneous blood flow,22 blood oxygen saturation, heart rate, blood pressure,23,24 and vascular assessments, including arterial stiffness 25…”
Section: Introductionmentioning
confidence: 99%